Aggregation‐Induced Emission and Efficient Solid‐State Fluorescence from Tetraphenylethene‐Based N, C‐Chelate Four‐Coordinate Organoborons. Issue 35 (19th July 2013) - Zhao, Zujin; Chang, Zhengfeng; He, Bairong; Chen, Bin; Deng, Chunmei; Lu, Ping; Qiu, Huayu; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> In it together: Thermally stable N, C‐chelate four‐coordinate organoborons were attained by grafting intramolecular B⋅ ⋅ ⋅N coordination into tetraphenylethene‐pyridine and ‐quinoline adducts. They exhibit aggregation‐induced emission characteristics (see figure), and high fluorescence quantum yields approaching unity in solid films.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>